The Transformation Of Private Higher Education Institution In Post-Reformation Indonesia 1998-2018: Case Studies Of Universitas Muhammadiyah Yogyakarta And Universitas Muhammadiyah Surakarta - Mudzakkir, Moh (2022)
This thesis examines the organisational transformation in Muhammadiyah higher education in post-reformation Indonesia 1998-2018. Specifically, this research took a case-study approach in investigating the experiences of UMY and UMS. Arguably, the institutional high point was when the two universities received the highest recognition with an “A” accreditation by the National Accreditation Board of Higher Education. Against this background, this study has three objectives: (i) to examine the key events of changes throughout two decades of organisational transformation in the two Muhammadiyah universities; (ii) to reveal generative mechanisms contributing to the transformation of two Muhammadiyah universities and; (iii) to explain commonalities and differences between the organisational transformation of the two universities.